The Relationship Between Government Stability and Foreign Investment for Selected Asean Countries - Pinjaman, Saizal; Kiong, Wong Vui; Mohd. Saudi, Nur Surayya binti (Malaysian Journal of Business and Economics (MJBE), 2019)
Abstract The current paper investigates the relationship between government stability and foreign direct investment for nine selected ASEAN countries. Based on the panel data analysis, it is identified that political stability, government effectiveness, and control of corruption are significant in explaining foreign direct investment while regulatory quality and rule of law are not. With the exception to government effectiveness, the remaining government stability variables that are significant show positive relationship with the inflow of capital where an increase in political stability and control of corruption lead to a higher level of foreign investment. The economic growth which is represented by the Gross Domestic Product is also identified to be a vital determinant of foreign investment. From the results, it is clear that government stability is an important factor in attracting foreigners to invest in the domestic markets of ASEAN and should not be taken lightly by the policymakers. Any adverse movement in government stability may disrupt foreign investment and ultimately affecting the economy.